'First and foremost, we are teachers, not refugees': Requalification measures for internationally trained teachers affected by forced migration. (March 2022) - Proyer, Michelle; Pellech, Camilla; Obermayr, Tina; Kremsner, Gertraud; Schmölz, Alexander
This article looks deeper into the educational careers and barriers faced by internationally trained teachers with refugee backgrounds. Highly skilled teachers experience among others formal barriers due to the two-subject regime in Austria. This study analyses the barriers and measures that disable or enable the re-qualification of internationally trained teachers who wish to continue their profession in Austria. Guided by a participatory approach laid out by Von Unger in 2014, this study taps into the needs of teaching professionals with refugee backgrounds and led to the development and implementation of a course. The course was compiled to provide educational knowledge as well as pedagogical training. Even though the completed subject of internationally trained teachers was recognised (apart from courses concerning didactics), the fulfilment of regular teacher training in Austria is seen as a conditio sine qua non . Hence, teachers with a different formal-educational background, irrespective of professional expertise, are seen as lacking education and/or skills. Considering that there is no worldwide consensus regarding the content and structure of teacher education, the implication of a lack of skills as well as the need for bridging programmes will be critically discussed from the participants' perspectives. This article offers insight into the transcultural implications of professionalism.